High Level Status Report to the IEO Evaluation of Fund's Recurring Issues. (Policy Papers; Policy Paper ;, 2017)
This is a high-level report on progress in addressing recurring issues identified by the Independent Evaluation Office (IEO). The Board endorsed the proposal in the Chairman's Summing Up for the Independent Evaluation Office Report on Recurring Issues from a Decade of Evaluation - Lessons for the IMF (BUFF/14/58, 6/11/14) that staff prepare a separate high-level report on the status of initiatives that address the recurring issues identified by the IEO, noting that the first staff report could be prepared within two years, followed by similar reports every five years thereafter. The September 2015 Management Implementation Plan set out the actions management would take to follow-up on the Board-endorsed recommendation. The IEO's 2014 evaluation of Recurring Issues from a Decade of Evaluation: Lessons for the IMF identified five recurring issues: a) Executive Board guidance and oversight; b) Organizational silos; c) Attention to risks and uncertainty; d) Country and institutional context; and e) Evenhandedness. This high-level report provides a broad account of actions taken to address these recurring issues since the publication of the 2014 IEO report; it is not intended as an exhaustive account of initiatives undertaken. Takeaways. The report concludes that the Fund has made progress in addressing the recurring issues identified by the IEO, and acknowledges the need for taking actions on an ongoing basis to achieve the related objectives. The discussion of the Management Implementation Plan (MIP) left open the question of whether subsequent reports should be prepared, perhaps every five years. The Evaluation Committee concluded that the forthcoming external evaluation of the IEO could look at the monitoring mechanisms more holistically, to provide further input into considering whether or not to continue the preparation every five years of this high-level report.